Involvement of an Inducible Fructose Phosphotransferase Operon in Streptococcus gordonii Biofilm Formation - Loo, C. Y. (American Society for Microbiology, 2003)
Oral streptococci, such as Streptococcus gordonii, are the predominant early colonizers that initiate biofilm formation on tooth surfaces. Investigation of an S. gordonii::Tn917-lac biofilm-defective mutant isolated by using an in vitro biofilm formation assay showed that the transposon insertion is near the 3′ end of an open reading frame (ORF) encoding a protein homologous to Streptococcus mutans FruK. Three genes, fruR, fruK, and fruI, were predicted to encode polypeptides that are part of the fructose phosphotransferase system (PTS) in S. gordonii. These proteins, FruR, FruK, and FruI, are homologous to proteins encoded by the inducible fruRKI operon of S. mutans. In S. mutans, FruR is a transcriptional repressor, FruK is a fructose-1-phosphate kinase, and FruI is the fructose-specific enzyme II (fructose permease) of the phosphoenolpyruvate-dependent sugar PTS. Reverse transcription-PCR confirmed that fruR, fruK, and fruI are cotranscribed as an operon in S. gordonii, and the transposon insertion in S. gordonii fruK::Tn917-lac resulted in a nonpolar mutation. Nonpolar inactivation of either fruK or fruI generated by allelic replacement resulted in a biofilm-defective phenotype, whereas a nonpolar mutant with an inactivated fruR gene retained the ability to form a biofilm. Expression of fruK, as measured by the β-galactosidase activity of the fruK::Tn917-lac mutant, was observed to be growth phase dependent and was enhanced when the mutant was grown in media with high levels of fructose, sucrose, xylitol, and human serum, indicating that the fructose PTS operon was fructose and xylitol inducible, similar to the S. mutans fructose PTS. The induction by fructose was inhibited by the presence of glucose, indicating that glucose is able to catabolite repress fruK expression. Nonpolar inactivation of the fruR gene in the fruK::Tn917-lac mutant resulted in a greater increase in β-galactosidase activity when the organism was grown in media supplemented with fructose, confirming that fruR is a transcriptional repressor of the fructose PTS operon. These results suggest that the regulation of fructose transport and metabolism in S. gordonii is intricately tied to carbon catabolite control and the ability to form biofilms. Carbon catabolite control, which modulates carbon flux in response to environmental nutritional levels, appears to be important in the regulation of bacterial biofilms.